(untitled) (Journal of Science and Technology, 2016)
Biochemical changes in the cocoa pulp and sweating during the traditional heap and sweat-box methods of fermentation of cocoa beans were studied Carbohydrate analysis showed the presence of fructose (5.06%), glucose (3.58%) and sucrose (6.17%) as the only free or fermentable sugars present in cocoa sweatings. Changes in levels of the free sugars m the sweatings were followed with fermentation time over 48 hours_ Sucrose was found to invert rapidly to glucose and fructose which were converted to alcohol and then acetic acid by yeast and acetic acid bacteria. Alcohol production started after 12 hours of fermentation and reached its peak at 30 hours and then declined after 30 hours. The pH of the cocoa pulp gradually increased while that of the cotyledons decreased simultaneously but both reached an ap-proximate value at the end offer-mental on by the traditional heap and sweat-box methods. A high buffering power of the sweatings was observed.